Creation of a contusion injury method for skeletal muscle in rats with differing impacts - Dantas,Milla Gabriela Belarmino (2017)
Abstract Purpose: To realize a morphological examination of the musculoskeletal tissue, assessing the effect of a contusion method for the production in rat gastrocnemius, comparing the inflammatory responses generated by different impacts. Methods: For the analysis of a contusion method, twelve female Wistar rats were distributed into four groups. The lesion was generated by 324 g of mass that was dropped from different predetermined heights for each group (30, 45, 60 and 70 cm). Results: In the analysis of musculoskeletal tissue, the response to injury varied according to the mass of the height drop onto the muscle. Only the group that was injured from 70 cm responded with uniform and severe inflammation, whereas the groups 30, 45 and 60 cm showed inflammation in some regions of the tissue with mild and moderate infiltrates. Conclusion: The method with the 324-gram mass dropped from a 70-cm height onto the gastrocnemius muscle of rats seems to be the most suitable for the production of muscle injury in these animals after 72 hours, showing an important inflammatory infiltrate.